Analisis Isi Lambung Ikan Mungkus (Sicyopterus cynocephalus: GOBIIDAE) untuk Menentukan Food and Feeding Habit di Sungai Padang Guci Kaur - Apriza Hongko Putra; Dian Fita Lestari; Sipriyadi Sipriyadi (Jurnal Biosilampari : Jurnal Biologi, 2023)
The aim of this research was to reveal the natural foods of S. cynocephalus from Padang Guci River, Kaur Regency. This research was conducted by using stratified random sampling by catching 75 individuals from its habitat divided by 3 stations such as Station I (upstream), Station II (middle stream) and Station III (downstream). Sampling was conducted using fishing trap and fishing net and then stomach dissection was done in Laboratory of Biology, FMIPA UNIB to identify food variety, body ratio, digestive tract ratio and frequency of food occurrences of fish samples (each 25 samples per station). In addition, water quality parameters were also measured. Based on the result, the data showed that there is a different in body development of mungkus fish which in Station I was positive allometry. In contrast, station II and III showed negative allometry. Based on frequency of food occurrence. The highest occurrence was Cosmarium decoratum (72 %) and the lowest was Synedra. All obtained food were classified as algae. Analysis of digestive tract and body ratio revealed that S. cynocephalus was categorized as herbivore fish with the ratio 3.72-5.34. The measurement of abiotic factor indicated that all parameters were still fulfil water quality standard to support the sustainability of Mungkus life in Padang Guci River.